Analyzing the Impact of Leadership Style and Organizational Culture on Teacher Performance with Motivation as an Intervening Variable - Maria Mellanie Rosari Chandra; Murtianingsih Murtianingsih; Widi Dewi Ruspitasari (Journal of Educational Management Research, 2026)
This study aims to examine the influence of leadership style and organizational culture on teacher performance, with motivation as an intervening variable. The research employed a quantitative approach using non-probability purposive sampling, involving 30 teachers as respondents. Data were collected through an online questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 to assess validity, reliability, and structural relationships. The findings reveal that leadership style does not have a significant direct effect on teacher performance or motivation, and organizational culture does not directly influence teacher performance. However, organizational culture has a positive and significant effect on motivation, and motivation significantly influences teacher performance. The mediation analysis indicates that motivation does not significantly mediate the relationship between leadership style or organizational culture and teacher performance. These results highlight that teacher motivation plays a central role in improving performance, implying that educational management should prioritize strategies that strengthen motivational factors alongside developing effective leadership practices and supportive organizational cultures.